Metodología para la implementación de estrategias de gestión del conocimiento en el programa Sofia Plus del Sena (2017)
The Knowledge management has become in a key process for organization development, it gives tools to accomplish with the strategic objectives set out in their policies, this document seeks to design a methodology, that unifies guidelines and strategies used for different organization across the globe, in the development of a knowledge management system for SOFIA Plus. For the development of research was considered the Organizational Culture of the institution being this an important factor for knowledge management, with the objective of improving team performance and response time for the development of new functionalities showing the relevance of SOFIA Plus as an essential system for academic education of many Colombians.